2019
DOI: 10.1002/fsn3.1308
|View full text |Cite
|
Sign up to set email alerts
|

Pro‐vitamin A carotenoids in East African highland banana and other Musa cultivars grown in Uganda

Abstract: Bananas and plantains (Musa spp.) are an important staple and food security crop in sub-Saharan Africa. In Uganda, where the consumption of East African highland banana (EAHB) is the highest in the world, the population suffers from a high incidence of vitamin A deficiency (VAD). Since the consumption of pro-vitamin A carotenoids (pVAC) made available through the food staple can help alleviate these ailments, we set out to identify the most suitable banana variety to use in future biofortification strategies t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
(128 reference statements)
1
4
1
Order By: Relevance
“…Composition and concentration of major carotenoids were obtained from HPLC analysis, while total carotenoids were derived from spectrophotometry data of α-carotene in Mas bananas and β-carotene in Raja bananas were 1,556.22 µg/100 g dw and 983.83 µg/100 g dw, respectively. Being the most marketable banana cultivar, Cavendish shows a low amount of β-carotene which corresponds to previous reports suggesting that Cavendish contained 21 to 290 µg/100 g dw of β-carotene [7,24,28].…”
Section: ■ Results and Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Composition and concentration of major carotenoids were obtained from HPLC analysis, while total carotenoids were derived from spectrophotometry data of α-carotene in Mas bananas and β-carotene in Raja bananas were 1,556.22 µg/100 g dw and 983.83 µg/100 g dw, respectively. Being the most marketable banana cultivar, Cavendish shows a low amount of β-carotene which corresponds to previous reports suggesting that Cavendish contained 21 to 290 µg/100 g dw of β-carotene [7,24,28].…”
Section: ■ Results and Discussionsupporting
confidence: 88%
“…Peak #3 was eluted at min 26.3 having λmax at 451 and 478 nm, thus, identified as β-carotene. Previous studies also reported these compounds as major carotenoids in other banana cultivars in several regions in the world, such as in Australia, Africa, and Asia [10,[24][25][26][27].…”
Section: ■ Results and Discussionmentioning
confidence: 73%
“…The difference in the composition could mainly be due to the genetic diversity among the Cucurbita species and the environmental conditions under which the pumpkins were grown. The α-carotene, trans-β-carotene, and the total carotenoid content observed in the pumpkin is by far higher than that reported in fruits like banana (Mbabazi et al, 2020). Therefore, considering that trans-β-carotene has 100% pro-vitamin A activity (Carvalho et al, 2014), accessions like Kab5, Kan22, Mit9, Mas16, Mit11 and Fort19 are promising sources of vitamin A. Pro-vitamin A carotenoid availability is of particular importance in developing countries where vitamin A deficiency (VAD) is a significant public health concern.…”
Section: Carotenoid Compositioncontrasting
confidence: 59%
“…In what ways, then, did the choices made in the lab, which were structured by this array of actants and their relations, imply a choice about who or what would become entangled and disentangled and in what ways? Bananas are of cultural and ritual importance in several African countries, as well as a pivotal source of income and food high in starch and some essential vitamins and minerals (Karamura et al 1999;Mbabazi et al 2020). In choosing bananas as the crop of choice and BXW as the problem to be addressed, the around 100 million people who depend on the cultivation of bananas, most of whom are small-scale farmers residing in East and Central Africa (Karamura, Karamura, and Tinzaara 2012;Tripathi, Mwangi et al 2009;Tripathi, Tripathi et al 2013), initially became entangled.…”
Section: Breeding Plant-people Entanglementsmentioning
confidence: 99%